Flawless ebook Flawless. - Shepard, Sara (Pretty Little Liars, 2009)
The #1 New York Times bestselling series that inspired the hit ABC Family TV show Pretty Little Liars and the upcoming HBO spin-off series Pretty Little Liars: Original Sin! Four pretty little liars have been very bad girls. Ever since the body of their former best friend was found, Aria, Hanna, Emily, and Spencer have been trying to figure out who could have killed her. But they've also been keeping some pretty big secrets...and now the mysterious "A" is threatening to reveal everything, including something so scandalous that the truth could ruin them forever. Perfect for fans of One of Us is Lying, The Cousins, and A Good Girl's Guide to Murder, this second book in Sara Shepard's #1 New York Times bestselling Pretty Little Liars series brings new twists to the thrilling and magnetically compelling world of Pretty Little Liars, where everyone's got something to hide, and no secret stays buried for long.